Development and Standardization of SCAN-C Test for Auditory Processing Disorders in Children - Keith, Robert W. (Journal of the American Academy of Audiology, 2000)
This paper reports on the development and standardization of SCAN-C: Test for Auditory Processing Disorders in Children-Revised. The revisions include new test instructions that have been reworded to make them easier for young children, aural stimuli presented on a compact disc, a revision of the Competing Words subtest, and the addition of a Competing Sentences subtest. Normative data on the new test were obtained on 650 children age 5 years, 0 months, to 11 years, 11 months. Analysis of new standardization data revealed systematic improvement in performance with increasing age. A new method of calculating the composite standard score gives equal weighting to each subtest of SCAN-C. Subtest test-retest reliability was substantially improved over the original SCAN, with SCAN-C correlations ranging from .65 to .82 for 5 to 7 year olds. Concurrent validity tests found that SCAN-C test results can be viewed with the same confidence as SCAN.Abbreviations: AFG = Auditory Figure-Ground, CD = compact disc, COMP = composite score, CS = Competing Sentences, CW = Competing Words, FW = Filtered Words
Keywords: Auditory Figure-Ground; central auditory processing disorder; Competing Sentences subtest; Competing Words; dichotic speech tests; Filtered Words